The Role of Nurses in Improving Adherence to Taking Medication in Tuberculosis Patients - Grace Carol Sipasulta; Rus Andraini (Miracle Journal Get Press, 2025)
Tuberculosis (TB) remains a significant global health threat, especially in Indonesia, which has one of the highest incidence rates. Effective treatment adherence is essential for controlling the disease. This study aimed to explore the relationship between the role of nurses and patient adherence in TB treatment, taking into account various social and economic factors. Methods Using a quantitative cross-sectional design, data were collected from 41 TB patients and nurses at Pondok Meja Health Center through the Morisky Medication Adherence Scale (MMAS-8) and semi-structured interviews. Data were analyzed using univariate statistical test, and bivariate with chi-square test. The results showed a strong correlation between patient adherence and the role of nurses as educators and motivators. Providing active education had a p-value of 0.002, while regular reminders had a p-value of 0.001. It can be concluded that the role of nurses in education, routine reminders, communication with families, and home visits have a significant relationship with the level of adherence of TB patients. Socioeconomic factors such as family support, access to health services, and economic conditions also play an important role in improving patient compliance.